Occurrence of persistent organic pollutants in sediments and biota from Portugal versus European incidence: A critical overview. Issue 3 (3rd March 2016) - Ribeiro, Cláudia; Ribeiro, Ana Rita; Tiritan, Maria Elizabeth
ABSTRACT: Persistent organic pollutants (POPs) are widespread compounds, such as organohalogenated compounds, polycyclic aromatic hydrocarbons (PAHs) and pesticides, which can be found in all types of environmental compartments. Their presence in the aquatic environment is a worldwide problem, with emphasis on sediments which act as depository and consequently as a source of hydrophobic, recalcitrant and harmful compounds. Besides, these pollutants might affect the reproduction and mortality of living organisms, diverging in their potential to bioaccumulate in tissues. The present paper aims to review the occurrence of POPs in sediments and biota from the coastal, estuarine and river areas of Portugal. The list of the studied compounds comprises organohalogenated compounds, PAHs, organometallic compounds, pesticides, sterols, fatty acids and pharmaceutical compounds. The contamination of sediments by various pollutants is presented, such as PAHs up to 7, 350 ng g −1 found in Sado estuary and polychlorinated biphenyls up to 62.2 ng g −1 in the case of sediments collected in Ria de Aveiro. The occurrence of these persistent toxic substances in sediments demonstrates aquatic contamination from agricultural, industrial and urban discharges and the concern about the potential risks to aquatic organisms, wildlife and humans. In fact, several classes of POPs have also been found in biota, such as polychlorinated biphenyls up to 810.9 ng g −1 in sentinel fish from the Douro River estuary and pesticides in bivalves from the Sado River estuary. The importance of further systematic research on sediments and biota is here highlighted to compare the contamination of these two reservoirs; to assess their spatial and temporal variation; and to determine other classes of POPs that were not investigated yet (e.g., industrial compounds, estrogens and many classes of pharmaceuticals).